Self-control of states: bridging social psychology to international relations discourses - Putra, Bama Andika (Frontiers in Sociology, 2024)
Why do states respond non-coercively in the face of crisis? Existing scholarship within international relations has stagnated in its conclusions regarding understanding this occurrence. This perspective article attempts to bridge the self-control theory of social psychology to provide a more nuanced understanding of why states self-refrain themselves from taking aggressive retaliatory foreign policies in state-to-state crises. It argues the importance of cognitive-affective units, such as encodings, expectancies, beliefs, goals, values, and self-regulatory plans, as the sociological interpretation of why states are committed to pursuing delayed rewards. It builds upon existing sociological theories adopted in international relations scholarship, such as state identities and role conceptions, and further considers the social psychology variables detrimental in self-control theories, and argues for its relevance to decompose the ability of a state to prioritize delayed gratification over immediate awards in tensions faced.